Achieving sustainable development goals through water and sanitation in sub-saharan africa: The role of industrialization - Mikala, Hermine Balouki (Asian Journal of Empirical Research, 2023)
Previous research has focused on the effect of infrastructure development on industrialization. However, the industrialization process can also be a source of social transformation. Thus, the objective of this study is to analyze the impact of industrialization on some indicators of sustainable development in particular the infrastructure development index, access to water and access to sanitation in sub-Saharan Africa (SSA). The data was collected from 27 countries in sub-Saharan Africa from 2000-2016. The Ordinary Least Square (OLS) and Generalized Least Square (GLS) methods were used to estimate the parameters of our econometric models. The results of the study show that industrialization has a positive and significant impact on all infrastructure indicators. Furthermore, tariff rates and political stability are also explanatory factors for the sustainable development indicators. Therefore, SSA countries which are mostly endowed with natural resources must increase their industrialization process in order to improve the social structures of their populations through the development of infrastructure. More precisely, the exploitation and transformation of their raw materials may help fight against underdevelopment through inclusive growth and the development of infrastructure.